A Review on the Role of SPRY4-IT1 in the Carcinogenesis - Ghafouri-Fard, Soudeh; Khoshbakht, Tayyebeh; Taheri, Mohammad; Shojaei, Seyedpouzhia (Frontiers in Oncology, 2022)
Sprouty RTK signaling antagonist 4-intronic transcript 1 (SPRY4-IT1) is a long non-coding RNA (lncRNA) encoded by a gene located on 5q31.3. This lncRNA has a possible role in the regulation of cell growth, proliferation, and apoptosis. Moreover, since SPRY4-IT1 controls levels of lipin 2, it is also involved in the biosynthesis of lipids. During the process of biogenesis, SPRY4-IT1 is produced as a primary transcript which is then cleaved to generate a mature transcript which is localized in the cytoplasm. SPRY4-IT1 has oncogenic roles in diverse tissues. A possible route of participation of SPRY4-IT1 in the carcinogenesis is through sequestering miRNAs such as miR-101-3p, miR‐6882‐3p and miR-22-3p. The sponging effect of SPRY4-IT1 on miR-101 has been verified in colorectal cancer, osteosarcoma, cervical cancer, bladder cancer, gastric cancer and cholangiocarcinoma. SPRY4-IT1 has functional interactions with HIF-1α, NF-κB/p65, AMPK, ZEB1, MAPK and PI3K/Akt signaling. We explain the role of SPRY4-IT1 in the carcinogenesis according to evidence obtained from cell lines, xenograft models and clinical studies.